Enhanced biomass production and proximate composition of marine microalga Nannochloropsis oceanica by optimization of medium composition and culture conditions using response surface methodology - Kumaran, Jisha; Poulose, Sunitha; Joseph, Valsamma; Bright Singh, Isaac S. (Animal feed science and technology, 2021)
•Nitrate concentration, temperature and pH influence the growth of N. oceanica.•RSM was used for optimize the high biomass and nutrient production in N. oceanica.•Media with 160 mg/L nitrate at 22 °C and pH 8.00 yielded 31 % higher biomass.•Culture conditions optimized for high carbohydrate, protein and lipid content.•Influence of interaction of culture variable on growth were analyzed using rsm. Nannochloropsis oceanica is a marine eustigmatophyte with high nutritional value, especially with high content of eicosapentaenoic acid that makes it an interesting aquaculture feed. The medium composition and culture conditions were optimized using response surface methodology for large scale culturing of this alga with improved productivity and nutritional value. Growth analysis of N.oceanica in five different meda (F/2; Walne’s; Miquel’s; L1 and K) showed the best growth in Walne’s medium in terms of cell count and specific growth rate. The effects of different concentrations of nutrients such as sodium nitrate, sodium dihydrogen phosphate and different temperature, pH, salinity and agitation speed on biomass concentration were analyzed using Plackett Burman experimental design, and the concentrations of significant medium components and culture conditions were further optimized for maximum biomass concentration and better proximate composition in terms of protein, lipid and carbohydrate using central composite design. The results showed that nitrate, temperature and pH had a positive effect on biomass production, protein concentration was significantly influenced by the interactions of pH and nitrate, and the carbohydrate and lipid concentrations were influenced by the interactive effects of pH, temperature and nitrate. The modified Walne’s medium with increased concentration of nitrate (160 mg/L) under optimum temperature 22 °C and pH 8, yielded a biomass of 760 ± 0.01 mg/L for a period of 10 days, or a 31 % increase compared to the yield under non-optimized conditions (580 ± 0.01 mg/L), and was accompanied by a significant change in the respective proximate composition of proteins, carbohydrates, and lipids. This work provides an efficient culture medium with appropriate nutrient concentrations and optimum culture conditions for the improved growth and proximate composition of N.oceanica.